The influence of pseudohalide ligands on the SIM behaviour of four-coordinate benzylimidazole-containing cobalt(ii) complexes. Issue 16 (12th April 2018) - Świtlicka, A.; Machura, B.; Kruszynski, R.; Cano, J.; Toma, L. M.; Lloret, F.; Julve, M.
Abstract : The structural and magnetic properties of three, mononuclear cobalt(ii ) complexes were reported. Abstract : Three, mononuclear complexes of the formula [Co(bmim)2 (SCN)2 ] (1 ), [Co(bmim)2 (NCO)2 ] (2 ) and [Co(bmim)2 (N3 )2 ] (3 ) [ bmim = 1-benzyl-2-methylimidazole] were prepared and structurally analyzed by single-crystal X-ray crystallography. The cobalt(ii ) ions in1–3 are tetrahedrally coordinated with two bmim molecules and two pseudohalide anions. The angular distortion parameter δ was calculated and the SHAPE program (based on the CShM concept) was used for1–3 to estimate the angular distortion from an ideal tetrahedron. The molecules of1–3 are effectively separated, and the values of the shortest distance of cobalt–cobalt are 8.442(6) and 6.774(8) Å for1, 10.349(8) and 10.716(8) Å for2 and 6.778(1) and 9.232(1) Å for3 . Direct current (dc) magnetic susceptibility measurements on the crushed crystals of1–3 were carried out in the temperature range 1.9–295 K. The variable-temperature magnetic data of1–3 mainly obey the zero-field splitting effect ( D ) of the 4 A2 ground term of the tetrahedral cobalt(ii ) complexes (2 D being the energy gap between the |±1/2〉 and |±3/2〉 levels of the spin). The analysis of their magnetic data through the Hamiltonian H = D [ S 2 z − S(S + 1)/3] + E ( S x 2 − S y 2 ) + gβHS led to the following best-fit parameters: g = 2.29, D = −7.5 cm −1 and E / D = 0.106 (1 ), g = 2.28, D = + 6.3 cm −1 and E / D = 0.007 (2 ) and g = 2.36, D = + 6.7 cm −1 and E / D = 0.090 (3 ). The signs of D for1–3 were confirmed by Q-band EPR spectra on powdered samples in the temperature range 4.0–20 K. Field-induced SIM behaviour was observed for1–3 below 4.0 K, and the frequency-dependent maxima of χ ′′M were observed for1 and only incipient signals of χ ′′M occurred for2 and3 . The values of the exponential factor ( τ 0 ) and activation energy ( E a ) for1–3 which were obtained from the Arrhenius plot suggest a single relaxation process characteristic of an Orbach mechanism.